Development of pineapple transgenic lines for the functional profiling of MIR535 gene family through the use of artificial microrna technology - Noor Hydayaty Md. Yusuf (2017)
Recently, artificial microRNA (amiRNA) technology has been widely used as a tool for creating loss-of-function mutants, especially in studies involving functional profiling, as it is able to silence genes or gene families in a specific manner. Artificial microRNA is derived by replacing the native mature miRNA duplex from an endogenous precursor miRNA (pre-miRNA) with synthetic ones. Like mature miRNA, amiRNA is designed with an ability to bind complementarily to its target _gene. The aim of the study was to develop amiRNAs using different backbones, which can then be used to silence the endogenous pineapple microRNA MIR535 family. In order to find the efficient amiRNA silencing in pineapple, stems of precursors were modified, as this will affect their processing efficiency by endogenous miRNA biogenesis. And, in order to silence the MIR535family, amiRNA was designed with the ability to bind to this mature region, as this increase the probability of it targeting more than one miR535 member. The amiRNAs were developed from newly discovered pre-miRNA from pineapple, and previously identified ones from Arabidopsis thaliana and 0ryza sativa. The first step involved the identification of the pre-miRNAs from pineapple transcriptomic libraries through in silico analysis. The amiRNAs were then designed to target theMIR535family, and subsequently inserted into precursors, and synthesized. The sequences of the expression cassette (promoter, enhancer, and terminator) were then fused into it, before transforming it into the plant expression vector, pCambia1303. Transgenes were then inserted into pineapple callus (MD2 hybrid) through Agrobacterium mediated transformation. Transgenic lines developed were used for expression profiling of amiRNAs and miR535's through stem-loop RT-qPCR. Three precursors found from pineapple (pre-miR156, pre-miR399, pre-miR2673) were modified (to have 20nt and S0nt stem) and used to carry amiRNA, together with the precursors of A. thaliana (pre-miR319) and 0. sativa (pre-miR528). Here, transgenic lines which have been inserted with these precursors showed the presence of amiRNA. Two pineapple precursors were found to be highly efficient in expressing amiRNA i.e. pre-miR156-50nt stem (Cq value of 20), followed by pre-miR2673 (Cq value of 24.4). The precursors from A. thaliana and 0. sativa were also found to be functional in pineapple, each with the Cq values of 20.8 and 23.8, respectively. Next, the ability of this amiRNA to silence the target gene (mature miR535b) was observed. In conjunction with the expression of amiRNA in transgenic callus, the expressions of target gene was found downregulated, with the highest silencing rate was by amiRNA produced from pre-miR156-50nt and pre-miR319. Also, the expressions of other mature miR535's were also quantified, and were found downregulated. In conclusion, the amiRNA technology was successfully developed for pineapple evidenced by the creation of loss-of-function mutant intheMIR535 family. The pineapple endogenous precursor was found capable to serve as backbone for amiRNA technology in pineapple. This study suggests that targeting 'common region' when designing amiRNA results in the silencing of several genes of the same family at the same time. Now, two highly efficient amiRNA precursors, pre-miR156 and pre-miR319 can be utilized in gene silencing- programs in pineapple.